Evaluation of the Conceptual Model on Shrubbiness-Desertification on Arid Rangelands - Torres, Y A; Busso, C A; Ithurrart, L S; Ambrosino, M L (Annals of Arid Zone, 2019)
Advancement of shrubbiness (increase in plant cover and density of woody species) on different environments world-wide has generated an increasing interest in the scientific community, particularly because of its association with the desertification process which is increasing, also at a world-wide level. There are two opposing positions, both of them validated by scientific evidences. The greatly accepted position recognizes shrubbiness as one of the mechanisms conducive to desertification in natural environments, cataloguing it as a negative process. A different view, based on recent studies, suggests that shrubbiness should be considered as a positive process because it may drive a reversal of desertification, depending on the environment and the species of shrub studied at a site. This review presented within this framework discusses the existing relationship between shrubbiness and desertification and proposes an approach that should be considered in future research. Key words: Shrubbiness, desertification, arid rangelands, arbuscular mycorrhiza, soil biological crusts.